Большая книга приключений для мальчиков: повесть / Э. Н. Веркин - Веркин Эдуард (Большая книга приключений, 2009)
Экземпляры: ДБ (20101228) / Инвентарный номер: 37258zzzzz / Цена: 160.00 / Сис.шифр: 84(2) / Авт.знак: В 31 / ГРНТИ: 17.82.31 / ББК: 84(2=Рус)